2012
DOI: 10.1155/2012/191245
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Cause of a Subcutaneous Nodule: A Case Report ofDirofilariaInfection

Abstract: Humans are not natural hosts of Dirofilaria; however, pulmonary or subcutaneous infections may occur through mosquitoes transmission. Patients presenting with simple subcutaneous nodules may not seek early medical attention, and hence systemic involvement through hematogenous spread may occur. Definitive diagnosis of Dirofilaria infection is made by histopathological examinations of the infected tissues. We report a patient with an incidental diagnosis of Dirofilaria infection confirmed by histopathological fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To et al [ 57 ] reported the detection of a novel species, “ Candidatus Dirofilaria hongkongensis,” which was responsible for three cases of human dirofilariasis in Hong Kong. Cheung et al [ 5 ] reported that a patient was diagnosed with Dirofilaria infection from a subcutaneous nodule on the right thigh. In 2013, Li [ 29 ] reported one case of human pulmonary dirofilariasis concurrent with intercostal neurilemmoma in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…To et al [ 57 ] reported the detection of a novel species, “ Candidatus Dirofilaria hongkongensis,” which was responsible for three cases of human dirofilariasis in Hong Kong. Cheung et al [ 5 ] reported that a patient was diagnosed with Dirofilaria infection from a subcutaneous nodule on the right thigh. In 2013, Li [ 29 ] reported one case of human pulmonary dirofilariasis concurrent with intercostal neurilemmoma in Taiwan.…”
Section: Discussionmentioning
confidence: 99%